The Role of Game Elements in Improving Jawi Skills through a Mobile Game ’G-Jawi’ - Mohd Rashid, Noor Asmina; Md Salleh, Shaharuddin; Md Noor, Norah (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The existence of a game-based mobile application in the field of education has largely helped students to be more interested and motivated to learn due to the presence of game elements in the apps which makes learning more interesting. The Jawi script is one of the subjects that is difficult to learn by younger generation since they do not apply the use of Jawi in their private lives. The inclusion of creative features such as game elements should attract students to explore the Jawi script. A pre- experimental one- group pre- test and post- test study was conducted in which a game-based mobile application for learning Jawi subject named G-Jawi was developed and tested among 20 primary school students in order to observe how the elements of the game in the mobile app impacted their Jawi spelling skills. The apps were also evaluated by 5 teachers and the findings shows that the game-based mobile application was able to improve the students’ performance. This finding was supported by positive results amongst the students which revealed a mean value for the post- test was higher than the pre- test of 89.00. In conclusion, the mobile games app has successfully enhanced student’s understanding of Jawi subjects compared to the traditional learning methods.